2015
DOI: 10.1007/s12034-015-0898-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of ZnO/TiO2 composite core/shell nanorod arrays by sol–gel method for organic solar cell applications

Abstract: ZnO/TiO 2 core/shell nanorod arrays were deposited on indium tin oxide (ITO) substrate via a facile sol-gel dip-coating process. Effects of solution pH for ZnO, annealing temperature, growth time and temperature on the physical properties of nanorods have been investigated. X-ray diffraction (XRD) analysis and scanning electron microscopy (SEM) were employed to characterize the structural and morphological properties of the prepared composite nanorods. XRD result revealed wurtzite structure of ZnO with a mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
2
11
0
3
Order By: Relevance
“…1d that the hexagonal prism structure of the modified ZnO NR is still clear and distinguishable owing to the shorter treatment time (5 min). The shorter treatment time may therefore avoid any deleterious effects on ZnO morphologies and surface energy, and further contribute to TiO2 crystal growth [21,23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1d that the hexagonal prism structure of the modified ZnO NR is still clear and distinguishable owing to the shorter treatment time (5 min). The shorter treatment time may therefore avoid any deleterious effects on ZnO morphologies and surface energy, and further contribute to TiO2 crystal growth [21,23]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lou et al [22] reported a PCE of 1.97% for QDSCs based on ZnO nanorods (NR) decorated with orthorhombic configuration TiO2 NPs by immersing ZnO film into a solution of tetrabutyl titanate (TBOT) in butyl alcohol for 5 min and annealing at 400°C for 30 min in argon atmosphere. Ahmadi et al [23] demonstrated vertically aligned ZnO NAs deposited with a layer of TiO2 by dip-coating into an ethanol solution of tetrabutyl orthotitanate and ethanolamine, and annealing at 450°C for 1 h. Interestingly, this TiO2 layer consisted of a mixed anatase and rutile structure phase. In view of these reports, we consider that the reaction parameters (the type of precursor solutions, dipping time, annealing temperature and time, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Another work reported on the synthesis and characterization of ZnO/TiO 2 core/shell NR arrays by sol–gel method for organic solar cell applications . The results showed that owing to smaller band gap and lower resistivity, the core/shell structure as an electron transport layer for inverted photovoltaic devices was more suitable than bare TiO 2 thin film.…”
Section: Coatings Of Zno Nanostructure Surfaces With Continuous Functmentioning
confidence: 99%
“…SCHNEIDER et al, 2014;FRANÇA et al, 2016). A utilização de outros óxidos como ZnO, Nb2O5, WO3, Al2O3, In2O3 dentre outros, assim como a dopagem dos mesmos ou a produção de compósitos envolvendo diferentes materiais têm levado a melhorias nas eficiências de processos fotoeletroquímicos e fotocatalíticos (CHENG et al, 2007;AKURATI et al, 2008;PAULA et al, 2014;YAN et al, 2014;AHMADI et al, 2015 A fase hexagonal do WO3 foi primeiramente obtida pela desidratação lenta de íons tungstato (GERAND et al, 1979). Tal fase é mais apropriada para aplicação como sensor de gás devido a sua estrutura de "túnel", enquanto a fase monoclínica do WO3 tem recebido uma maior atenção na aplicação como fotocatalisador (BAMWENDA e ARAKAWA, 2001;CHENG et al, 2007;HONG et al, 2009).…”
Section: Introductionunclassified
“…A crescente evolução nos métodos de síntese desses materiais, assim como a produção de filmes finos dos mesmos também merece destaque. Diferentes processos, como a decomposição, precipitação ácida, hidrotermal, sol-gel, dentre outros, se mostraram bastante eficientes na preparação simples e barata de tais compostos, assim como a técnica de automontagem ou "Layer-by-Layer" tem sido amplamente utilizada na obtenção de filmes finos com composição e morfologia controlada (PATROCINIO et al, 2014;PAULA et al, 2014;AHMADI et al, 2015;TAN et al, 2015;NUNES et al, 2017).…”
Section: Introductionunclassified